Barriers and outcomes of an evidence-based approach to diagnosis and management of chronic obstructive pulmonary disease (COPD) in Australia: a qualitative study. (30th September 2016) - Dennis, Sarah; Reddel, Helen K; Middleton, Sandy; Hasan, Iqbal; Hermiz, Oshana; Phillips, Rosemary; Crockett, Alan J; Vagholkar, Sanjyot; Marks, Guy B; Zwar, Nicholas
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is commonly managed in primary care but there is poor awareness of evidence-based guidelines and the quality and interpretation of spirometry is suboptimal. Objectives: The aims of this qualitative study were to explore how an intervention involving case finding and management of COPD was implemented, and the extent to which the GPs and practice nurses (PNs) worked in partnership to diagnose and manage COPD. Methods: Semi-structured interviews with PNs ( n = 7), GPs ( n = 4) and patients ( n = 26) who had participated in the Primary care EarLy Intervention for Copd mANagement (PELICAN) study. The Theoretical Domains Framework was used to guide the coding and analysis of the interviews with PN and GPs. The patient interviews were analysed thematically. Results: PNs developed technical skills and understood the requirements for good-quality spirometry. However, many lacked confidence in its interpretation and felt this was not part of their professional role. This was reflected in responses from the GPs. Once COPD was diagnosed, the GPs tended to manage the patients with the PNs less involved. This was in contrast with PNs' active role in managing patients with other chronic diseases such as diabetes. The extent to which the GPs and PNs worked in partnership to manage COPD varied. Conclusions: PNs improved their skills and confidence in performing spirometry. Beliefs about their professional role, identity and confidence influenced the extent to which PNs were involved in interpretation of the spirometry results and managing the patient in partnership with the GP.